PEMETAAN ISOPHREATIC KONTUR UNTUK MENDUGA ARAH ALlRAN CEMARAN LINDI DI BAWAH PERMUKAAN TANAH (STUDI KASUS PADA TPA SAMPAH GALUGA) - Teti Syahrulyati; Surjono H. Sutjahjo; Soedodo Hardjoamidjojo (Jurnal Keteknikan Pertanian, 2007)
ABSTRACTThis research proposed to asses seepage flow pattern at TPA Geluga. Hydrogeology isophreatic contour could be used to asses seepeqe flow pottern. Mapping was based on weter table  elevation measurements In the areas. Isophreatic contour was made by inter polating several points measurements. Seepage flow pattern could be defined from isophreatic map. From isophreatic map there were 2 flow patterns at TPA Galuga: seepage flow pattern to North and sinked seepage flow pattern caused by it. The area was permanently polluted bymeans of leachate sinked seepage flow pattern  Keywords: seepage, leachate, isophreatic mapDiterima: 27 April 2007; Disetujui: 19 Agustus 2007